Socioeconomic Development Effects on Soil Toxic Elements in Beijing-Tianjin-Hebei: Using Enhanced STIRPAT Model - Siyu Wang; Yizhong Huan; Shun Li; Zhonglin Xu; Riqi Zhang; Yang Zhao; Qijia Lou; Guangjin Zhou (Ecosystem Health and Sustainability)
Soil pollution by potentially toxic elements (PTEs) is a persistent environmental challenge aggravated by urbanization processes. This study investigated the 21-year (2000 to 2021) spatiotemporal evolution of 7 key PTEs (Pb, Cr, Cd, Cu, Zn, Ni, and As) in the Beijing-Tianjin-Hebei region and explored the driving socioeconomic factors using an enhanced STIRPAT (stochastic impacts by regression on population, affluence, and technology) model considering population, economy, technology, urbanization, and transportation. Results showed a continuous accumulation of PTEs with significant increases in Cu, Zn, Ni, and As concentrations (P < 0.001). Health risks associated with economic growth intensified initially but slowed after 2015, indicating emerging pollution control effects. The dominant socioeconomic drivers shifted across stages: industrial restructuring (2000 to 2005), population–technology synergy (2006 to 2010), green infrastructure (2011 to 2015), and the economic–industrial complex (2016 to 2021). These findings link socioeconomic transformations to soil PTE dynamics, offering insights for stage-specific pollution management in rapidly developing megaregions.